Endogenous Credit Spreads and Optimal Debt Financing Structure in the Presence of Liquidity Risk. (2nd June 2016) - Lütkebohmert, Eva; Oeltz, Daniel; Xiao, Yajun
Abstract: We present a structural model that allows a firm to effectively manage its exposure to both insolvency and illiquidity risk inherent in its financing structure. Besides insolvency risk, the firm is exposed to rollover risk through possible runs by short‐term creditors. Moreover, asset price volatilities are subject to macroeconomic shocks and influence creditors' risk attitudes and margin requirements. Credit spreads are derived endogenously depending on the firm's total default risk. Equity holders have to bear the rollover losses. An optimal debt structure that maximises the firm's equity value is determined by trading off lower financing costs and higher rollover risk.